Hippocampal PPARα Plays a Role in the Pharmacological Mechanism of Vortioxetine, a Multimodal-Acting Antidepressant - Wang, Yuan; Gu, Jiang-Hong; Liu, Ling; Liu, Yue; Tang, Wen-Qian; Ji, Chun-Hui; Guan, Wei; Zhao, Xin-Yi; Sun, Ying-Fang; Xu, Da-Wei; Jiang, Bo (Frontiers in Pharmacology, 2021)
As a well-known multimodal-acting antidepressant, vortioxetine is thought to aim at several serotonin (5-HT) receptors and the 5-HT transporter. However, recently more and more proteins besides 5-HT are being reported to participate in the antidepressant mechanism of vortioxetine. As a widely known nuclear hormone receptor, peroxisome proliferator activated receptor α (PPARα) possesses transcriptional activity and is very important in the brain. Several reports have suggested that hippocampal PPARα is implicated in antidepressant responses. Here we speculate that hippocampal PPARα may participate in the antidepressant mechanism of vortioxetine. In this study, chronic unpredictable mild stress (CUMS), chronic social defeat stress (CSDS), behavioral tests, the western blotting and adenovirus associated virus (AAV)-mediated gene knockdown methods were used together. It was found that vortioxetine administration significantly reversed the inhibitory actions of both CUMS and CSDS on the hippocampal PPARα expression. Pharmacological blockade of PPARα notably prevented the antidepressant actions of vortioxetine in the CUMS and CSDS models. Moreover, genetic knockdown of PPARα in the hippocampus also significantly blocked the protecting effects of vortioxetine against both CUMS and CSDS. Therefore, the antidepressant effects of vortioxetine in mice require hippocampal PPARα.